Strengthening Digital Literacy Skills through the “Digital Learning Hub” Program in Ngasem Village - Anwarri, Kenza Amalia Putri; Lutfina, Erba; Udayanti, Erika Devi; Mellati, Pita (LPPM ITB AAS Indonesia Surakarta, 2024)
The high level of juvenile delinquency in Ngasem village is known to originate from the lack of parental attention, access to content on the internet that should not be consumed, and the lack of positive activities for students. Meanwhile, dropping out of school in Ngasem village was not only due to decreased motivation to learn but also because parents could not pay for their children to continue their education. From the survey results, it is known that people who are not working are because after the Covid-19 pandemic, people do not have either soft skills or hard skills. From analyzing these problems, PPK Ormawa Biro Sistem Informasi PSDKU Udinus Kediri proposed a solution to improve digital literacy for children in Ngasem village. The form of increasing digital literacy is packaged in the Digital Learning Hub program by implementing 6 literacy corners. The proposed digital literacy training are FunCoding Literacy, Animation, Graphics, Content Making, TrainingPreneur, and Parenting and Sex Education. From the series of PPK Ormawa activities, it can be concluded that the Digital Learning Hub program can be used to improve creative thinking and computation for participants. The implementation of coding training activities and basic programming concepts achieved a satisfaction target of more than 90%, which means that this activity was enthusiastically welcomed by the participants.